Unveiling the impact of artificial intelligence on economic performance: The mediating roles of leadership and employee engagement - Alateeg, Sultan; Almutairi, Ngeyan Nega; Diab, Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the interplay between artificial intelligence (AI), leadership, employee engagement, and economic performance within the manufacturing sector of Saudi Arabia. Adopting a cross-sectional design, data was collected in March 2025 from employees using an online survey questionnaire. Convenience sampling was employed to gather responses from a diverse workforce, ensuring accessibility and feasibility. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS to examine the hypothesized relationships. The findings reveal that AI significantly influences leadership and employee engagement, highlighting its role as a strategic enabler in enhancing decision-making, innovation, and employee motivation. Leadership, in turn, positively impacts economic performance, while employee engagement shows a strong direct effect on economic performance. The study also identifies significant indirect effects, where AI influences economic performance through leadership and employee engagement. These results underscore the importance of integrating AI with effective leadership practices and a culture of engagement to drive organizational success. The study highlights AI’s indirect effects on organizational dynamics and offers practical insights for leveraging AI to enhance leadership, employee engagement, and economic outcomes. For organizations in the manufacturing sector and beyond, the findings highlight the need for a holistic approach to AI implementation, combining technological innovation with human-centric strategies to achieve sustainable growth and competitive advantage.